2017
DOI: 10.1111/ajps.12316
|View full text |Cite
|
Sign up to set email alerts
|

When Are Agenda Setters Valuable?

Abstract: Why do industries donate money to legislative campaigns when roll-call votes suggest that donors gain nothing in return? I argue that corporate donors may shape policy outcomes by influencing powerful agenda setters in the early stages of lawmaking. On the basis of a new data set of more than 45,000 individual state legislator sessions , I document how agenda control is deemed valuable to legislators and groups seeking influence on policy. Employing a difference-in-differences design, I assess the revealed pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…This suggests that committee membership exerts its own effect on the donations of interested groups, separate from the selection of interested members onto these committees. The increase in donations downstream is also consistent with the finding that firms operating within the purview of a given committee target the chair of that committee more than other committees (Fouirnaies ).…”
Section: Committee Membership Increases Contributions From Relevant Gsupporting
confidence: 79%
“…This suggests that committee membership exerts its own effect on the donations of interested groups, separate from the selection of interested members onto these committees. The increase in donations downstream is also consistent with the finding that firms operating within the purview of a given committee target the chair of that committee more than other committees (Fouirnaies ).…”
Section: Committee Membership Increases Contributions From Relevant Gsupporting
confidence: 79%
“…This suggests that committee membership exerts its own effect on the donations of interested groups, separate from the selection of interested members onto these committees. The increase in donations downstream is also consistent with the finding that firms operating within the purview of a given committee target the chair of that committee more than other committees (Fouirnaies 2017).…”
Section: Figure 1 Effect Of Committee Membership On Contributions Frosupporting
confidence: 79%
“…Concentrations of economic power are seen to corrupt democracy (Acemoglu et al ; Bartels ; Easterly ), although, depending on the author, this may subsequently be viewed as causing decreases or increases in economic freedom. This theoretical foundation is somewhat at odds with the empirical political science finding little effects of money on politics (e.g., Levitt ), although recent empirics have cast this into doubt (Fouirnaies ; Fouirnaies and Hall ). Generalized reviews of institutions and inequality can be found in Chong and Calderon () and Savoia, Easaw, and McKay ().…”
Section: Surveying the Literaturementioning
confidence: 97%